Latrophilins function as heterophilic cell-adhesion molecules by binding to teneurins: regulation by alternative splicing - Boucard, Antony A; Maxeiner, Stephan; Südhof, Thomas C (The Journal of biological chemistry, 2014)
Latrophilin-1, -2, and -3 are adhesion-type G protein-coupled receptors that are auxiliary α-latrotoxin receptors, suggesting that they may have a synaptic function. Using pulldowns, we here identify teneurins, type II transmembrane proteins that are also candidate synaptic cell-adhesion molecules, as interactors for the lectin-like domain of latrophilins. We show that teneurin binds to latrophilins with nanomolar affinity and that this binding mediates cell adhesion, consistent with a role of teneurin binding to latrophilins in trans-synaptic interactions. All latrophilins are subject to alternative splicing at an N-terminal site; in latrophilin-1, this alternative splicing modulates teneurin binding but has no effect on binding of latrophilin-1 to another ligand, FLRT3. Addition to cultured neurons of soluble teneurin-binding fragments of latrophilin-1 decreased synapse density, suggesting that latrophilin binding to teneurin may directly or indirectly influence synapse formation and/or maintenance. These observations are potentially intriguing in view of the proposed role for Drosophila teneurins in determining synapse specificity. However, teneurins in Drosophila were suggested to act as homophilic cell-adhesion molecules, whereas our findings suggest a heterophilic interaction mechanism. Thus, we tested whether mammalian teneurins also are homophilic cell-adhesion molecules, in addition to binding to latrophilins as heterophilic cell-adhesion molecules. Strikingly, we find that although teneurins bind to each other in solution, homophilic teneurin-teneurin binding is unable to support stable cell adhesion, different from heterophilic teneurin-latrophilin binding. Thus, mammalian teneurins act as heterophilic cell-adhesion molecules that may be involved in trans-neuronal interaction processes such as synapse formation or maintenance.